Od…czytanie „Świata według T. S. Spiveta” Reifa Larsena. Część II: punkty węzłowe dwóch perspektyw interpretacyjnych – liberackiej oraz koncepcji świata jako gry - Szymor‑Rólczak, Marta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
In the second part of the paper devoted to the multidimensional analysis and interpretation of the novel by Reif Larsen, I present another perspective of interpretation – the category of the description of narrative texts related to the concept of the text as a game, manifesting a strong feedback relationship with the theory of liberature. I argue that both these approaches applied to a certain group of artistic operations complement each other perfectly, providing a more comprehensive, multi‑faceted explanation of a literary text. The part that comprises the analysis and interpretation of verbal and non‑verbal elements of the novel by R. Larsen is preceded by the exploration of the paradigm of the text as a game, indicating definitional heterogeneity in this regard.